Development of Mobile Learning-Based Learning Resources to Improve Multimedia Student's Creative Problem Ability as Details Fieldwork Practice - Monica, Elyana Frisca; Widiyanti, Widiyanti; Marsono, Marsono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Currently, the world is being hit by an outbreak of coronavirus disease (covid-19), including in Indonesia. Covid-19 entered Indonesia in December 2019 with 4,231,046 positive cases as of October 13, 2021. Major changes occurred in various fields, both economic, social, and social politics and education. Vocational High School is a secondary education unit that is prepared to enter the form of employment and develop a professional attitude. One of the SMK programs is the Field Work Practice (PKL). One of the obstacles experienced by students in the multimedia field is when street vendors do not deliver materials and practices that are following DUDIKA's needs. Seeing the current condition of the covid pandemic, the debriefing is carried out online, therefore it is necessary to have a mobile learning-based learning resource that is considered more attractive, effective, and efficient, especially in the current new normal era. The development of learning resources based on mobile learning uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The results of this study indicate that a mobile learning-based learning resource for the debriefing of street vendors is appropriate to be used as a supporting medium for independent learning, according to the tests carried out on material experts, media experts, small group trials, and large group trials. From the two material experts, the presentation results were 81.67% with a very decent category without the need for revision. From the three material experts, the percentage results were 80% with a decent category without the need for revision. The results of the small group test got a presentation of 81% and for the large group, it was 81.58% which was very feasible without the need for revision. Improved creative problem-solving skills were improved using pretest and posttest by testing using paired sample t-test. The results of the test showed that the output pair sig (2-tailed) value was 0.000 > 0.05, so it can be said that there is a difference between the experimental class pretest data and the experimental class posttest data, which means that the application of mobile learning-based learning resources affects the results student learning before the learning resource is given and after it is given.